The theory of Cr3+ pairs of D3h symmetry - Barry, Kevin Richard (1981)
A novel approach to the problem of describing interacting magnetic ions has been put forward by Stevens. The work contained herein offers the first major test of the new formalism; applied specifically to binuclear systems in which magnetic Cr3+ ions occur in discrete pairs of D3h symmetry. Each interacting pair is regarded as a unit; wavefunctions suitable for describing the pair are constructed in determinantal form. The wavefunctions of D3h symmetry are used to define the unperturbed Hamiltonian. An effective Hamiltonian is then used to obtain the energy levels in a restricted energy range. (The region of the 2TI levels of the single Cr3+ ion). A set of selection rules is derived. With direct comparison with experimental results the success of theoretical predictions is estimated. Certain interval relations are obtained. There is no first order spin-orbit splitting. Through second order perturbation the maximum values of the spin-orbit coupling constant are found for three materials. The theoretical Zeeman splittings are stated.